2020
DOI: 10.1108/scm-12-2019-0466
|View full text |Cite
|
Sign up to set email alerts
|

“I have just returned from the moon:” online survey fraud

Abstract: Purpose The purpose of this paper is to provide a comprehensive review of the respondents’ fraud phenomenon in online panel surveys, delineate data quality issues from surveys of broad and narrow populations, alert fellow researchers about higher incidence of respondents’ fraud in online panel surveys of narrow populations, such as logistics professionals and recommend ways to protect the quality of data received from such surveys. Design/methodology/approach This general review paper has two parts, namely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Accordingly, we ensured our respondents were mainly CEOs and managing directors. We received 223 responses; 23 of these response were eliminated due to (1) a high proportion of missing answers, and (2) the responses having been completed in less than a third of the median time taken for others to complete the survey (Brazhkin, 2020). Although we have included attention check questions to minimize low-quality responses, we have not found any low-quality responses for further elimination.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Accordingly, we ensured our respondents were mainly CEOs and managing directors. We received 223 responses; 23 of these response were eliminated due to (1) a high proportion of missing answers, and (2) the responses having been completed in less than a third of the median time taken for others to complete the survey (Brazhkin, 2020). Although we have included attention check questions to minimize low-quality responses, we have not found any low-quality responses for further elimination.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…First, the measures used in the present study were generic and might not accurately capture pregnant women's picky eating or disordered eating, which should be addressed in future studies using pregnancy‐specific measures. Second, pregnant women in our study were recruited online; thus, findings may suffer from common issues observed with online survey methodologies (e.g., fraud; Brazhkin, 2020). The present findings should be replicated in pregnant women recruited offline (e.g., from hospitals) with in‐person screening and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Fraudulent behavior relates to self‐misrepresentation or the use of bots to maximize rewards. Generally, surveys of narrow populations are more prone to fraud, which reduces data quality (Brazhkin, 2020). Methods to reduce or detect satisficing and fraudulent behavior include attention checks, bogus questions, open‐ended questions, self‐reports of effort, response times, analyzing choice response patterns and selection of non‐substantive responses, digital fingerprinting, as well as many other methods (Aguinis et al, 2021; Baker et al, 2010; Brazhkin, 2020; Chmielewski & Kucker, 2020; Lawler et al, 2021; Teitcher et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, surveys of narrow populations are more prone to fraud, which reduces data quality (Brazhkin, 2020). Methods to reduce or detect satisficing and fraudulent behavior include attention checks, bogus questions, open‐ended questions, self‐reports of effort, response times, analyzing choice response patterns and selection of non‐substantive responses, digital fingerprinting, as well as many other methods (Aguinis et al, 2021; Baker et al, 2010; Brazhkin, 2020; Chmielewski & Kucker, 2020; Lawler et al, 2021; Teitcher et al, 2015). 2 One recent study (Goodrich et al, 2023) details experiences of conducting online surveys targeted towards narrow populations (e.g., posting to social media site) that received a high number of fraudulent responses.…”
Section: Literature Reviewmentioning
confidence: 99%